Metode Layanan Bimbingan Konseling terhadap Masalah pribadi Sosial Siswa di SMP Negeri 2 Sedong Kabupaten Cirebon - Jawahir, Adi (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2021)
Exclusive social guidance for students is a guidance in dealing with and solving personal-social problems, for example: adjustment, facing problems, using counseling service methods for exclusive social problems in students which are expected to make it easier for counseling teachers to solve social personal problems. learners. This research is a qualitative research which aims to find out how the counseling guidance service method for the personal social problems of students, namely adjustment, facing feuds and relationships for students who are in class VII and VIII of SMP N 2 Sedong Cirebon Regency in the academic year 2018 / 2019. The subject of this research means the counseling guidance teacher and students, while the object is how the counseling guidance service method to the direct social dilemmas of students at SMP N 2 Sedong Cirebon Regency. Data collection techniques using the method of observation, interviews and documentation. What will happen from this research are the methods used by counseling teachers in dealing with adjustment problems include: student observation methods, student calling methods, lecture methods, home visit methods and student monitoring methods. dealing with feuds include: methods of calling students, methods of visiting students and methods of calling parents. The methods used by counseling teachers to handle social dilemmas include: the lecture method which consists of the classical lecture method and the individual lecture method.